2021
DOI: 10.3390/ma14216712
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Behavior, Microstructural Properties, and Freeze–Thaw Behavior of Tailing Recycled Aggregate Concrete with Waste Polypropylene Fiber Addition

Abstract: To improve the high brittleness of recycled aggregate concrete containing iron ore tailings (TRAC), the feasibility of adding polypropylene fiber (PPF) to TRAC was studied by performing a compression stress–strain curve test, scanning electron microscope characterization, and a freeze–thaw cycle test. The results indicated that PPF had a beneficial impact on reducing the brittleness of TRAC. With the increase in PPF content, the peak strain increased, the elastic modulus decreased, and the peak stress and ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…These dispersed PPFs could effectively play a positive role, such as connecting the substrate and transferring the load. Figure 10b shows the crisscrossing and disorderly distribution of PPFs in the matrix, which eventually formed a three-dimensional distribution network within the concrete [34]. This structure could effectively reduce the stress concentration and the generation and development of cracks in the concrete, which had a positive impact on the macromechanical properties [64].…”
Section: Scanning Electron Microscopy Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…These dispersed PPFs could effectively play a positive role, such as connecting the substrate and transferring the load. Figure 10b shows the crisscrossing and disorderly distribution of PPFs in the matrix, which eventually formed a three-dimensional distribution network within the concrete [34]. This structure could effectively reduce the stress concentration and the generation and development of cracks in the concrete, which had a positive impact on the macromechanical properties [64].…”
Section: Scanning Electron Microscopy Analysismentioning
confidence: 98%
“…PPFs do not participate in the hydration reaction of the recycled concrete, which improved the mechanical properties of the concrete through physical connections that inhibited the generation and development of pores and improved the pore structure [32,33]. Xu et al [34] performed a scanning electron microscopy (SEM) analysis of recycled concrete. The results showed that the PPFs transferred the load to the surrounding matrix through bridging cracks, which effectively improved the mechanical properties of the recycled concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The fracture toughness is determined using the critical stress intensity factor (KIC) by using the following equation [45,46]: ],…”
Section: Fracture Toughnessmentioning
confidence: 99%
“…As a consequence, cracks may be induced when these pressures finally exceed the tensile strength of the concrete. With increasing freezing and thawing cycles, this damage will be more severe, and the concrete stripping off will arise [45]. about by PP fibers and the interpenetrating organic-inorganic structure, all of which had the beneficial effect of inhibiting the appearance of cracks.…”
Section: Mass Loss Ratementioning
confidence: 99%
See 1 more Smart Citation